Multilateral Collaboration in Canadian Intergovernmental Relations: The Role of Procedural and Reciprocal Norms. Issue 4 (12th January 2018) - Schertzer, Robert; McDougall, Andrew; Skogstad, Grace
Abstract: This article investigates the conditions that facilitate multilateral collaboration in Canadian intergovernmental relations (IGR). It argues that durable patterns of multilateral collaboration require particular procedural and reciprocal norms. These norms develop through structured and repeated interactions among intergovernmental actors as they learn over time how to share jurisdictional responsibility for a policy field to their mutual advantage. We trace the development of procedural and reciprocal norms of multilateral collaboration in three policy fields (agriculture, immigration, and labor markets), and the role these norms played in constraining unilateral government action in recent IGR. We find that procedural and reciprocal norms of multilateral collaboration are associated with intergovernmental agreements that combine an overarching multilateral framework to pursue common/pan-state priorities with supplementary bilateral agreements to accommodate more specific goals of different provincial governments.